NEW SEMI-BLIND APPROACH TO OPTIMIZE TURBO DECODING FOR A CAUCHY - A., Chemsa*; , Labbi2 Y.; m, Hettiri; , Ghendir1 S.; R., . Ajgou1 , (جامعة الوادي university of eloued, 2018)
Knowledge of the noise parameters that contaminate the signal sent is very important for many communication systems. In this work, we propose a new method to estimate the dispersion parameter of a symmetric α-stable impulse noise (SαS) of Cauchy, from the received signal only at the iterative decoder (turbo decoder). This method is based on the FLOS (Fractional Lower Order Statistics) and the probability that binds the received signal and the signal sent in BPSK modulation (Binary Phase Shift Keying). The results obtained, in terms of RMSE (Root Mean Square Error) and BER (Bit Error Rate) show the precision and the efficiency of our approachKnowledge of the noise parameters that contaminate the signal sent is very important for
ARTICAL
Keywords: Cauchy impulse noise SαS, dispersion parameter, FLOS, RMSE, BER